Responses of Indigenous People to the Climate Changes: A Case Study of the Surels of Dolakha District of Nepal (Patan Pragya, 2021)
This paper has examined the way the Surels, an indigenous group inhabiting in Suri village of Dolakha district, perceive climate change and also has attempted to document their adaptive strategies to the changes brought about by climate change and global warming. These peoples have developed uniquely insightful ways of observing, interpreting, and responding to the impacts of climate changes through interacting and closely linking their lives with their surroundings. They clearly linked climate change with the changes in the weather patterns over the years indicating erratic rainfall patterns, advancing monsoon, advancing summer and spring, shorter and warmer winter, drier and hotter summer. This paper argues that these people observe and encounter climate and environmental changes immediately and use traditional knowledge and survival skills to adapt to these changes as they occurred. They have devised, though it is not well documented, useful coping mechanisms—modifying cropping pattern and crop types, community-based afforestation and forest management initiatives, improve water management, involvement of community organization in water management and seasonal migration to India- to respond and reduce climate induced risks and impacts which have enabled them to achieve stable livelihoods in their environment.